Fixed income analysis - Fabozzi, Frank J. (CFA Institute investment series., 2007)
In the Second Edition of Fixed Income Analysis, financial expert Frank Fabozzi and a team of knowledgeable contributors provide complete coverage of the most important issues in fixed income analysis. Now, in Fixed Income Analysis Workbook, Second Edition, Fabozzi offers you a wealth of practical information and exercises that will solidify your understanding of the tools and techniques associated with this discipline.